Study on the size effect of elastic modulus of rock considering the joint spacing - Zhao, Tao; Hu, Gaojian (Frontiers in Materials, 2023)
The relationship between the rock’s elastic modulus and deformation characteristics, affected by joint spacing and ductility, was not determined. This study investigates the size effect of the elastic modulus of rock with parallel joints using numerical simulation and regression analysis. The results showed an exponential relationship between elastic modulus and spacing of parallel joints and a negative exponential relationship between elastic modulus and rock size. The characteristic size of elastic modulus has a power function relationship with the parallel joints spacing, and the characteristic elastic modulus of rock has a power function relationship with the parallel joints spacing. The general and specific forms of these relationships are provided. Establishing these relationships allows for predicting and calculating the elastic modulus of the mine rock mass and serves as a reference for the deformation analysis of the rock.